Improving the installation of renewable heating technology in UK social housing properties through user centred design. Issue 7 (November 2015) - Moore, Natalie; Haines, Victoria; Lilley, Debra
Social housing organisations are increasingly installing renewable energy technologies, particularly for the provision of heating and hot water. To meet carbon reduction targets, uptake and installation must allow occupants to use the technology effectively. This paper describes research which investigated the service of installing heat pumps into UK social housing properties, from both landlords' and tenants' experiences. Adopting a user centred design approach, the research was in three phases: an exploration study to investigate landlords' and tenants' experiences of heat pump installation and use; refinement and development of the requirements for improved service delivery, primarily technology introduction and control; and the development and initial evaluation of an information leaflet as a key touchpoint in the service delivery. Recommendations for improved service delivery, to enable heat pumps to be accepted and used more effectively, are presented, as well as reflection on the process of applying user centred design in this context. In a relatively immature area of industry, installations to date have been heavily focused on technical aspects. This paper provides an insight into the human aspects of the service delivery of heat pumps in social housing, providing designers and social housing landlords with insight about how to improve the service.